Effects of microwave heating on dielectric and piezoelectric properties of PZT ceramic tapes - Chen, Yun-Tien; Sheu, Ching-Iuan; Lin, Shih-Chin; Cheng, Syh-Yuh (My University, 2008)
Commercial lead zirconate titanate (PZT) perovskite powders were used to fabricate ceramic tape and then sintered by microwave and conventional methods. Both dielectric and piezoelectric properties of PZT ceramic tapes were studied in terms of sintering process. X-ray diffraction analysis (XRD) and scanning electron microscopy (SEM) show the PZT perovskite phase with smaller grain size and dense microstructure can be obtained at a lower sintering temperature by microwave process. It was also observed that shrinkage ratio and bulk density of the tapes sintered at 800 degrees C were obtained about 19% and 7.46 g/cm(3) by the microwave heating method, respectively, that is corresponding to those values of sintered PZT tapes at 950 degrees C by conventional process. Moreover, the dielectric constant and maximum permittivity are increased about 30% as compared with conventional processing method. The experimental results demonstrated that the characteristics of the PZT tapes could be significantly improved by microwave heating method. These results demonstrate that such a simple approach can upswing the piezoelectric and dielectric properties of these tapes by using microwave process with a short heating time. (C) 2007 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: dielectric properties; piezoelectric properties; PZT; microwave heating